INOVASI PEMBELAJARAN MENULIS PUISI MELALUI METODE BERBASIS PENGALAMAN DI KELAS X TKRO 1 SMK KB PUSDIKPAL - tasya arin prautami; teti sobari; aditya Permana (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
Writing skills as a part that is considered important, namely writing poetry skills. However, the conditions that occur are in fact many who experience difficulties. Learning strategies are needed in creating a pleasant atmosphere. Experience-based learning model is an approach where students as the center start with the premise that people learn based on experience. The purpose of this study is to describe the effect of using experience-based methods on learning to write poetry in class X TKRO 1 SMK KB Pusdikpal. The research method used in this research is PTK. The instruments used were test and non-test. Data collection techniques include observation, interviews and documentation. Aspects to be assessed include: Accuracy of themes and meanings, diction, rhymes, power of imagination, mandate. The pre-cycle result, the average score of writing poetry was still low, namely 61.1, in the first cycle the class average score increased to 69.5, while in the second cycle, the average score reached 78.4. The increase obtained is if the average value of learning to write poetry in the pre-cycle compared to the first cycle has increased by 8.4, while in the second cycle it is 8.9. With the results obtained in cycle II, it can be seen that the innovation of learning to write poetry in class X TKRO 1 SMK KB Pusdikpal using experience-based learning methods is considered to be able to improve learning outcomes in writing poetry.